UN VISTAZO A LA INNOVACIÓN SOSTENIBLE: FORJANDO UN FUTURO RESILIENTE (Revista de Diavulgación L'esprit Ingénieux, 2024)
Dear readers,Aware of your profound interest in the progress and well-being of our region, it is an honorto present you with a new issue of the L’Esprit Ingénieux journal that delves into the wondersof sustainable engineering and its impact on our environment. At a time when the urgentneed to preserve our planet becomes more evident, it is essential to explore and disseminateways in which technical innovation, especially engineering, can converge with environmentalprotection and social responsibility. This will shape a future that is environmentally responsibleand committed to social progress. This edition of our journal provides a global view of the advancementof innovation in various engineering fields, while also emphasizing a strong social andenvironmental commitment. It is heartening to see that the articles align with the humanisticcharacter of Universidad Santo Tomás. All the authors, in their writings, demonstrate a deepsocial and environmental commitment. In this issue of the magazine, with five research articles,we will be invited to reflect upon, learn about, and explore technical advancements in civil andenvironmental engineering, while being critical of the social and economic needs in Colombia.